Dinamika Pengalaman Psikologis selama Pembelajaran Kolaboratif dengan Aktifitas Seni: Sebuah Penelitian Studi Kasus menggunakan Photo Elicitation Interview dalam Klasikal Pelatihan Dasar CPNS di PPSDM Kemendikbudristek - 'Alwan, Faiz Fatihul; Indrajati Kunwijaya (LP3M IAI Al-Qolam, 2025)
The basic training for civil servant candidates is aimed at strengthening national character. At the PPSDM of the Ministry of Education and Culture, collaborative learning with art activities is conducted during the classical training sessions. Preliminary data from this study revealed that collaborative learning with art activities has generated positive emotions and reduced anxiety among trainees. Therefore, the objective of this research is to explore the psychological dynamics experienced by trainees during collaborative learning with art activities in the Classical Training for Civil Servant Candidates at PPSDM Kemendikbudristek. This study employs a qualitative approach with a case study design involving three civil servant candidates participating in the training. Data is collected using a photo-elicitation interview method to achieve a deeper understanding. Subsequently, the data is analyzed using an interactive data analysis approach, including coding, theme identification, and theory construction. The findings of this research indicate that, in addition to fostering positive feelings and reducing anxiety, feeling secure about people, roles, and responsibilities plays a dynamic role in the meaningfulness of collaborative learning. Combined with art activities, the meaningfulness of collaborative learning can serve as a platform for building a sense of belonging as a civil servant.